Life Cycle Assessment of Municipal Solid Waste Management System in Kathmandu, Nepal - Ranabhat, Ramesh (Journal of Advanced College of Engineering and Management, 2016)
Due to rapid urbanization, ever increasing population, limited resources and industrialization all-inclusive, the environmentally habitual management of municipal solid waste has become a global challenge. According to report of the National Population Census 2011, growth rate of Nepalese Population is 1.4 percent per annum with population density estimated at 181 per sq. KMs. Solid waste management inNepal, the current practice of the illegal dumping of solid waste on the river banks has created a serious environmental and public health problem. The focus of this study was to carry out the magnitude of the present SWM problems by identifying the sources, types, quantities, dangers and opportunities they pose. It will be helpful to examine the adequacy of the existing institutional arrangements and implement a strategic and operational plan for SWM and to establish the EASEWASTE data base of municipal solid waste management system inKathmandu City,Nepal. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 97-106